2004
DOI: 10.1016/s1054-139x(04)00052-7
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism dimensions in children and adolescents with anorexia nervosa

Abstract: The Spanish version of the CAPS and the PSPS showed good psychometric properties. A percentage of 40% of adolescent patients with anorexia nervosa show high Self-oriented perfectionism and Perfectionistic self-presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
14

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 0 publications
3
54
0
14
Order By: Relevance
“…9 Specifically, in adolescent samples, self-oriented and socially prescribed perfectionism are two dimensions of perfectionism associated with higher total Eating Attitudes Test (EAT) scores. 7,10,11 A study aimed at determining the nature of the relationship between perfectionism and psychopathological conditions, including eating disorders, found that an increase in concern over mistakes was associated with anorexia and bulimia but not with other disorders. This suggests that perfectionism may be more predictive of disordered eating than of other pathologies, including obsessive-compulsive disorder, and may work in concert with low self-esteem (SE) in women.…”
Section: Introductionmentioning
confidence: 99%
“…9 Specifically, in adolescent samples, self-oriented and socially prescribed perfectionism are two dimensions of perfectionism associated with higher total Eating Attitudes Test (EAT) scores. 7,10,11 A study aimed at determining the nature of the relationship between perfectionism and psychopathological conditions, including eating disorders, found that an increase in concern over mistakes was associated with anorexia and bulimia but not with other disorders. This suggests that perfectionism may be more predictive of disordered eating than of other pathologies, including obsessive-compulsive disorder, and may work in concert with low self-esteem (SE) in women.…”
Section: Introductionmentioning
confidence: 99%
“…Societal Expectations for Women anxiety, depression, and suicide, this finding is not surprising (Blankenstein, et al, 1993;Castro et al, 2004;Delisle, 1986;Flett, et al, 1991;Hewitt & Flett, 1991a).…”
Section: External Pressures Internal Pressuresmentioning
confidence: 96%
“…While the aforementioned research suggests the existence of positive behavioral outcomes and perfectionism, the bulk of the available literature connects perfectionism and maladaptive behaviors (Alden, et al, 1994;Ashby & Rice, 2002;Bieling, et al, 2004;Blankstein, et al, 1993;Blatt, 1995;Castro et al, 2004;Chang, 1998;Chang & Rand, 2000;Chang, et al, 2004;Cockell, et al, 2002;Flett, Hewitt, Blankstein, & Gray, 1998;Flett, Hewitt, Blankstein, & O'Brien, 1991;Hewitt, Flett, & Ediger, 1996;Hewitt & Flett, 1991a;Hewitt & Genest, 1990;Sherry, et al, 2003). The likelihood of perfectionists to set high standards and work to obtain them is not behavior by itself that is identified as pathological (Frost, et al, 1990).…”
Section: Perfectionism As Maladaptivementioning
confidence: 99%
See 2 more Smart Citations